Learning Management of Female Students with Dual Roles at State Islamic University - Alwis Alwis; Rahmi Diana; Doli Witro; Rifqi Nurdiansyah; Raid Alghani (Ta'dib, 2023)
This article aims to reveal learning management for State Islamic University students with dual roles, namely studying and managing the household. This study used a descriptive-quantitative method using a sample of eight female students pursuing undergraduate education at a State Islamic University in West Java through a convenience sampling technique. Data collection techniques are through observation, interviews, and documents. At the same time, the data analysis technique uses a technique popularized by Miles and Huberman, namely data condensation, data display, and concluding. The study results show that it is challenging to discipline female students with multiple roles in time management. However, following the flow, adapting, dividing the time, and trying to do each of these roles well. However, the achievement can not be felt optimally. Therefore, it is sporadic for female students to have multiple roles in determining the management of their study time. As for trying to continue to design good learning time management, it will be able to discipline in moving forward and achieving predetermined goals